Application of organic-inorganic hybrids in lithium batteries. (December 2020) - Cheng, N.; Ren, L.; Xu, X.; Du, Y.; Dou, S.X.
Abstract: To address the increasing energy demand, rapid consumption of non-renewable fuels, and serious environmental problems, it is very crucial to develop efficient, economical, and environmental-friendly energy conversion/storage devices. Lithium batteries are one of the most attractive and encouraging candidates. However, up to date, their performance is still far from satisfactory. Hence, researchers have been focusing on developing suitable materials as efficient electrodes, separators, electrolytes, etc ., to improve their performance. Among all the diverse materials, organic-inorganic hybrids have attracted much attention because they not only possess characteristics of both the organic and inorganic parts but also own specific properties generated from their synergistic effects. It is feasible to obtain organic-inorganic hybrids with desirable properties through the proper hybridization of suitable organic and inorganic precursors. Herein, we made a brief summary of the categories, synthesis strategies, and application of organic-inorganic hybrids in lithium batteries, with special emphasis on the construction of favored organic-inorganic hybrids and their derivatives as efficient electrodes and separators for lithium batteries. These organic-inorganic hybrids have demonstrated their potential to enhance the performance of lithium batteries and other energy conversion/storage devices to the satisfactory level. Graphical abstract: Image 1 Highlights: This paper focuses on the review of categories, synthesis, and application of organic-inorganic hybrids in lithium batteries. Advantages and drawbacks of current organic-inorganic hybrids in lithium batteries have been briefly summarized.